An analysis of the readiness of Surabaya city government to implement international medical tourism - Ramadhani, Tasya (Journal of Commerce, Management, and Tourism Studies, 2025)
Surabaya has great potential to develop international medical tourism, but the city is still in the early stages of this process. One of the challenges is that the preparation for launching this project has been ongoing for a long time, starting from the COVID-19 period. This study aims to analyze the efforts made by the Surabaya City Government in preparing the development of international medical tourism, focusing on the city’s readiness to enter the international market. This research uses an evaluative approach by adopting the Uppsala Model to understand and assess the stages of readiness and the actions that have been taken. The findings show that the Surabaya Tourism Office has taken an important step by looking for local travel agencies with international networks, working together with hospitals, clinics, and laboratories in Surabaya. Bappedalitbang also plays a leading role in coordinating and strengthening collaboration among related sectors in developing medical tourism. Based on the Uppsala Model analysis, Surabaya is expected to gain a better understanding of international market needs by collecting in-depth information about medical political regulations, patients’ socio-cultural backgrounds, and the types of medical services needed, including economic and tourism-related aspects, especially from patients in Southeast Asian countries. This will serve as an important foundation for improving the city's readiness and accelerating its expansion into the international medical tourism market.